Mereduksi Kecanduan Pornografi Menggunakan Teknik Restrukturisasi Kognitif - M. Alfa Yusro Nursahid; Siti Muyana (Universitas PGRI Palembang, 2024)
This Guidance and Counseling Action Research was conducted with the aim of overcoming students' porn addiction through individual counseling services with cognitive restructuring techniques. The method used in this research is the Classroom Action Research (CAR) method in Guidance and Counseling. The subject of this study was a student of SMP N 2 Sewon Class VII who was taken by purposive sampling. This research was conducted in 2 cycles of stages with the administration of tests in each cycle. Data collection techniques are interviews and pornography addiction scales. The method of data analysis used quantitative descriptive data analysis techniques with standard deviation and percentage. The results of this guidance and counseling action research based on the results of pre-test, post-test I and post-test II on the aspects of onlien pornography = 34 (high) to 23 (quite low) to 18 (low); talking porn = 23 (quite high) to 17 (quite low) to 13 (low), and influencing factors = 50 (high) to 37 (quite low) to 28 (low). The results of data analysis obtained from this study indicate a reduction in pornography addiction after individual counseling services using cognitive restructuring techniques. The results of this study can be used as a reference for handling pornography addiction in schools.